2018
DOI: 10.1101/248286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex chromosome trisomies are not associated with atypical lateralisation for language

Abstract: AimIndividuals with a sex chromosome trisomy (SCT) have disproportionate problems with language compared to nonverbal skills. This may result from disruption to the typical left hemisphere bias for language processing. We tested the hypothesis that SCTs would be associated with reduced left lateralisation for language.MethodIn a cross-sectional design, language laterality was measured during an animation description task using functional transcranial Doppler ultrasonography (fTCD). Data were available for 75 c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Language lateralization in sex chromosome trisomies has also been investigated using functional imaging. One study found that KS men were less lateralized than a control group (van Rijn et al, 2008), but this finding has not been replicated (Wallentin et al, 2016), and a recent study failed to find atypical lateralization for any of the sex chromosome trisomies (Wilson and Bishop, 2018b).…”
Section: Language and Gender In Disorders And In The Diseased Brainmentioning
confidence: 98%
“…Language lateralization in sex chromosome trisomies has also been investigated using functional imaging. One study found that KS men were less lateralized than a control group (van Rijn et al, 2008), but this finding has not been replicated (Wallentin et al, 2016), and a recent study failed to find atypical lateralization for any of the sex chromosome trisomies (Wilson and Bishop, 2018b).…”
Section: Language and Gender In Disorders And In The Diseased Brainmentioning
confidence: 98%
“…In addition, handedness and language laterality were assessed. Results from laterality assessments were unremarkable and are not considered further here ( Wilson & Bishop, 2018a ; Wilson & Bishop, 2018b ).…”
Section: Methodsmentioning
confidence: 99%
“…In dyslexic brains, hypoactivation of the left occipital-temporal region during language tasks ( 317 ) and underdevelopment of the left frontal gyrus have been observed, especially among populations that use logographic letters, such as Chinese ( 318 ). Brains of KS have been reported to show a similar lack of dominance when processing language tasks ( 319 , 320 ), although not all ( 321 ).…”
Section: Expectation Mismatch On Perceptual Input Will Lead To Uneven...mentioning
confidence: 99%